ENTRUSTING ZAKAH (ALMS) ADMINISTRATION TO THE GOVERNMENT: A REVIEW OF HISTORICAL STUDY AND SHARI’AH PERSPECTIVE - Abdulsoma Thoarlim; Mursalin Maggangka; Mohamamed Muneer’deen Olodo al Shafi’i (Jurnal Ekonomi dan Bisnis, 2016)
This study analyses one of the sacred trusts which Allah the Almighty has assigned to Muslimleaders or the government in the country, i.e. the administration of obligatory alms (zakah)led by the government and how it is seen from the historical perspective and Islamic law.The study applies a type of qualitative research which tends to the documents analysis. Thestudy focuses on the issue on aversion of some Muslims in the country to entrust their alms(zakah) administration to their government or its representatives due to the weakness of lawenforcement and the lacking of their trust to them over the years. Accordingly, the issue of thezakah distribution which is still individually practiced today, where they distribute it directly tothe recipients (asnaf), whereas the Shari’ah law does not give anyone the right or mandateto collect and distribute it in this way. Therefore, this significant issue should be resurrectedand resolved due to the fact that many people in the country does not comply it very well. Thisproblem actually caused by their lack of knowledge of zakah obligation, objectives of shari’ah(maqasid al-shari’ah) in zakah administration, zakah philosophy and its history.Keywords: Alms, Collection, Distribution, Shari’ah, Government.